2016
DOI: 10.1103/physreva.94.023602
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the vortex-clustering transition in a confined two-dimensional quantum fluid

Abstract: Clustering of like-sign vortices in a planar bounded domain is known to occur at negative temperature, a phenomenon that Onsager demonstrated to be a consequence of bounded phase space. In a confined superfluid, quantized vortices can support such an ordered phase, provided they evolve as an almost isolated subsystem containing sufficient energy. A detailed theoretical understanding of the statistical mechanics of such states thus requires a microcanonical approach. Here we develop an analytical theory of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 82 publications
(136 reference statements)
3
43
0
Order By: Relevance
“…For charge-neutral atoms in a closed trap without external fields, a potentially related clustering transition has been reported [88,89]. Onsager's point-vortex model [79] implies a maximum entropy state in which an equal number of elementary vortices and anti-vortices are randomly distributed in the system.…”
Section: Three-body-collision Induced Vortex Lossmentioning
confidence: 99%
“…For charge-neutral atoms in a closed trap without external fields, a potentially related clustering transition has been reported [88,89]. Onsager's point-vortex model [79] implies a maximum entropy state in which an equal number of elementary vortices and anti-vortices are randomly distributed in the system.…”
Section: Three-body-collision Induced Vortex Lossmentioning
confidence: 99%
“…The successes of the recent experimental developments have also spawned novel theoretical investigations [13,[34][35][36][37][38][39][40][41][42][43][44][45]. In addition to visual inspection, the presence of Onsager vortices has been associated with indicators such as the vortex dipole moment [13,34], vortex clustering measures [7,8,36,37,40], or a peak in the power spectral density of incompressible kinetic energy [8,13,38,46].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of vortex clustering is theoretically investigated by the GP equation and Monte Carlo calculation [145,146,148,149]. Recently, Simula et al found that such a negative temperature state is dynamically formed through the evaporative heating of vortex when the disk-shaped flat potential is used [146] 1 .…”
Section: Formation Of the Onsager Vortex Of 2d Qtmentioning
confidence: 99%
“…There are many studies for 2D QT [129,130,138,139,140,141,142,143,144,145,146,147,148,149], some of which discuss the possibility of the inverse cascade in QT. To our understanding, the existence of the inverse cascade in QT is controversial.…”
Section: Inverse Cascade Of 2d Qtmentioning
confidence: 99%